Horror a thematic history in fiction and film - Jones, Darryl 1967- (Arnold, 2002)
Starting with questions about the nature of horror, this book offers a history of the genre. Using exmples from key Gothic texts or the Romantic period and more recent popular novels and films, it includes chapters on 'Mad science'; vampires and the undead; and madness and psycho-killers.
Keywords: Griezelfilms; Griezelromans; Horror films -- History and criticism; Horror in literature; Horror tales -- History and criticism; Horrorfilm; Horrorliteratur